Palliative chemotherapy for pancreatic adenocarcinoma: a retrospective cohort analysis of efficacy and toxicity of the FOLFIRINOX regimen focusing on the older patient - Anne Katrin Berger; Georg Martin Haag; Martin Ehmann; Anne Byl; Dirk Jäger; Christoph Springfeld (BMC Gastroenterology, 2017)
Abstract Background Pancreatic cancer occurs more frequently in older patients, but these are underrepresented in the phase III clinical studies that established the current treatment standards. This leads to uncertainty regarding the treatment of older patients with potentially toxic but active regimens like FOLFIRINOX. Methods We conducted a retrospective analysis of patients treated according to the FOLFIRINOX protocol at our institution between 2010 and 2014 with a focus on older patients. Results Overall survival in our cohort was 10.2 months. Only 43% of patients did not need dose adaptations, but dose reductions did not lead to an inferior survival. We did not find evidence that patients aged 65 years and older deemed fit enough for palliative treatment had more toxicities or a worse outcome than younger patients. Conclusion We conclude that treatment with the FOLFIRINOX protocol in patients with pancreatic cancer should not be withhold from patients solely based on their chronological age but rather be based on the patient’s performance status and comorbidities.